TAMIL FILM AND SUSTAINABILITY: A NEW TURN FROM ILLUSION TO REALITY - AN ANALYSIS - Panbuselvan, P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Gender-based discrimination, climate change catastrophes, and expanding populations are the most concerning factors of the twenty-first century. The entire world requires rapid action to control the current challenge. To meet the world’s population’s needs and to improve the lives of every living being, there must be a disciplined livelihood to deal with the problems that man creates. The benefits of the seventeen sustainable goals structured by the United Nations General Assembly in 2015 bring an admirable global notice to society. Each is distinct in its way and extremely valuable and beneficial to humans and other living beings. Artists of various kinds contribute a lot to achieving these sustainability goals through their artistic creations. Congenially, a participatory outlook on these goals is more prominently seen in many regional film industries in Indian cinema. Among them, the Tamil film industry has recorded these 17 targeted concepts at different times and in variant ways of life. Eliminating poverty, providing quality education, reducing inequality, establishing good health and well-being, and other SDG themes can be appropriately traced in Tamil cinema from its early days. This paper analyses the SDG as depicted in two female-centric Tamil films, 36 Vayadhinile (2015) and Raatchasi (2019). Both films portray refreshing characters battling towards a strong hope for sustainable societal growth and uncover the major SDG goals on the screen for the audience’s cognizance. The core possibilities of pursuing Sustainable Development Goals likely with tangible results are identified in the paper with a thorough study of the several SDG plans portrayed in the films.